A SOCIAL HISTORY OF KNOWLEDGE: PROBLEMS AND PERSPECTIVES - Burke, Peter (Revista Prâksis, 2010)
Ten years ago I published a book about the social history of knowledge in Europe from Gutenberg to Diderot, in other words from the invention of printing until the publication of the French Encyclopédie that Diderot edited, a book in many volumes that was not only a collective presentation of what was known at the time but also an instrument in the service of the Enlightenment.